Heat [videorecording (DVD)] - Smith, Martin (Martin E.); Smith, Martin (Martin E.); Smith, Martin (Martin E.) (PBS Home Video, 2008)
Under pressure from governments, green groups, and investors, big businesses, such as the oil and coal companies, electric utilities, and automobile manufacturers, are promising to reshape their approach to the environment, climate change, and carbon emissions. Shows how some corporations around the world are fighting to fend off new regulations while others are repositioning themselves to meet these challenges. Visits the melting glaciers of the Himalayas, Chinese coal companies, Indian SUV makers, and American oil giants, among other locations.